(untitled) (Emancipação, 2026)
Digital technologies of information and communication are the source of multiples human advancements, in work optimization, in medicine, sciences and other dimensions of our daily lives. Capitalism use these technologies to implement a new business model, that of platforms, based on data exploration and manipulation to offer services that are executed by digital labor to maximize platform’s gains. The set of systems and practices are a new form of colonialism, and they structure the digital work in the relations between the Global North and Global South. The general objective of this essay is to study the predatory and colonialist practices of platforms as related to citizenship exclusion. The methodology was based on bibliographical and documental research, articulated with empirical evidences and experiences of digital labor. Platforms are structures that offer limited agency while curtailing attempts to change their status quo. Digital colonialism is the main theoretical reference. Analysis revealed a trove of relational qualities (i.e. those that occur during the use of the platforms) that support the main proposal that they impede citizenship. Platforms explore digital labor (i.e. that executed according to colonizing practices). That is to say, low-income people who already live in precarious conditions). The offer no sufficient income, no labor protections, terrible working conditions. Information asymmetry is used to surveillance and punishment. They are opaque and are not accountable. Their practices deepen inequalities, widen exclusion and preclude citizenship.